GAME THEORY ON MARKETING MIX STRATEGY BETWEEN BUKALAPAK, SHOPEE AND TOKOPEDIA - Niko Dwi Haryanto; Ervina Islamiati (Journal of Business Administration Economics & Entrepreneurship, 2022)
Technological developments are growing rapidly and over time it makes many activities easier such as transacting on the marketplace, several marketplaces in Indonesia, namely Bukalapak, Shopee and Tokopedia, intense competition makes management must be able to understand the concept of game theory. The design of this research is descriptive statistical analysis. The data collection method used in this study is a questionnaire. The data processed in the study are primary data obtained through the results of questionnaires distributed to respondents using a Likert scale. The variable of this research is the marketing mix which consists of product, price place, promotion, proses, people physical evidence, people opinion, and political power. The analysis technique used is validity test, reliability test and game theory matrix. The respondents obtained were 117 people, and the number of each user from Bukalapak, Shopee and Tokopedia was the same, namely 39 people. The results of this study indicate that the game value of Bukalapak and Shopee is 0.4, Bukalapak and Tokopedia is -0.1 and Shopee is -0.6. Bukalapak's strategy against Shopee is people, while Shopee is political power, then Bukalapak's strategy against Tokopedia is people, while Tokopedia is people opinion, and Shopee's strategy against Tokopedia is political power, while Tokopedia is people opinion.Keywords:   Strategy Management, Game Theory, Marketplace.